Qingchang Suppository Ameliorates Colonic Vascular Permeability in Dextran-Sulfate-Sodium-Induced Colitis - Sun, Boyun; Yuan, Jianye; Wang, Shiying; Lin, Jiang; Zhang, Wanjun; Shao, Jiadong; Wang, Ruiqing; Shi, Bei; Hu, Hongyi (Frontiers in Pharmacology, 2018)
Ulcerative colitis (UC), with a long course and repeated attack, severely affects patient’s life quality and increases economic burden all over the world. However, the concrete causes and mechanisms of UC are still unclear, but it is generally considered that many factors participate in this process. Qingchang Suppository (QCS) has been used in treating rectitis and colitis for about 30 years in Shanghai, China. Its satisfactory clinical effects have been proved. The aim of this study is to investigate the effect and mechanisms of QCS on colonic vascular endothelial barrier in dextran sulfate sodium (DSS)-induced colitis. The results indicated that increased vascular permeability (VP) appeared earlier than increased intestinal epithelial permeability (EP) in the process of DSS-induced colitis. QCS attenuated colonic tissue edema, vascular congestion and inflammatory cell infiltration. QCS inhibited the elevation of MPO, TNF-α and IL-6 levels in colon tissues and alleviated the microvascular damage induced by DSS. QCS also improved colonic hypoxia and decreased the expression of VEGF, HIF-1α and iNOS. These results revealed that QCS can reduce colonic VP and can improve vascular endothelial barrier function maybe by regulating the VEGF/HIF-1α signaling pathway.